1999
DOI: 10.1097/00007632-199902150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Mechanical Stretch Stress Increases the Growth Rate and Collagen Synthesis of Nucleus Pulposus Cells In Vitro

Abstract: Mechanical stress on nucleus pulposus cells promotes the proliferation of cells and alters the properties of intervertebral disc cells. This study may reflect the adaptation of the intervertebral disc to increased motion and stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…The device consisted of a computer-controlled vacuum unit, a culture well plate with a flexiblepolystyrene culture well bottom coated with type I collagen (Flex I, Flexercell International Corp., McKeesport, PA, USA), and another culture well plate with a non-deformable culture well bottom made of the same materials as Flex I (Flex 11, Flexercell International Corp., McKeesport, PA, USA). Application of a vacuum provides a hemispherically downward deformation to the flexible Flex I bottom, resulting in a non-homogenous strain profile with a maximum at the Table 2 Sequences of RT-PCR primers used in the present study periphery and a geometric decline toward zero at the center or the culture well bottom [2,4,9,19,21]. The cells were placed in Flex I and Flex I1 culture well plates at a density of 1 x 10' cellslwell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device consisted of a computer-controlled vacuum unit, a culture well plate with a flexiblepolystyrene culture well bottom coated with type I collagen (Flex I, Flexercell International Corp., McKeesport, PA, USA), and another culture well plate with a non-deformable culture well bottom made of the same materials as Flex I (Flex 11, Flexercell International Corp., McKeesport, PA, USA). Application of a vacuum provides a hemispherically downward deformation to the flexible Flex I bottom, resulting in a non-homogenous strain profile with a maximum at the Table 2 Sequences of RT-PCR primers used in the present study periphery and a geometric decline toward zero at the center or the culture well bottom [2,4,9,19,21]. The cells were placed in Flex I and Flex I1 culture well plates at a density of 1 x 10' cellslwell.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy-two h after the cells were cultured, the culture medium was replaced with DMEM supplemented with 0.5'%1 FBS, 50 yglml L-ascorbic acid (Sigma Chemical, St. Louis, MO, USA), penicillin G (100 Ulml). and streptomycin (100 pglml) to keep the cells quiescent for 24 h. At the beginning of the present study, the cells in the Flex I plates were subjected to 10-s cycles of 20%) elongation and 10 s of relaxation at 37 "C in a 5% COz incubator by referring to a previously described protocol [21]. This preliminary study revealed that the cells could not survive under this condition over 96 h. The stretching protocol was, then, modified.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last few decades, several studies have shown that changes in the mechanical environment of the disc can result in remodeling, breakdown, and reorganization of the extracellular matrix [ 1, 7,13,[18][19][20][21][22]29,32,33,35,41,44], leading in some cases to signs of accelerated disc degeneration. Such work forms the *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The fine balance between synthesis of components and the breakdown of tissue determines the composition of the matrix; tissue integrity is thus dependent on the activity of the nucleus pulposus cells [53]. In vivo [20,43] and in vitro [14] environmental factors such as mechanical stress [30,34] and nutrient levels have been found to affect matrix composition, presumably by affecting macromolecule biosyntheAbstract It has long been known that very acidic conditions can be found in degenerate discs. The effect of these acid conditions on matrix turnover are, however, unknown.…”
Section: Introductionmentioning
confidence: 99%